The application of memo-motion to industrial operations - Norbury, C. J. (College of Aeronautics, Cranfield, 1954)
Memo-Notion, or Spaced Shot Photography, was introduced as a tool of Work Study Dr. Mundel, then of Purdue University, in 1946, as a means of reducing the cost of film analysis on long operations by using a camera driven by a geared down electric motor, giving exposures every second. Since its introduction Memo-Motion has been applied to a limited extent in the U.S.A., but it is not known to be in use at all in England.